2007
DOI: 10.1130/ges00088.1
|View full text |Cite
|
Sign up to set email alerts
|

Curvature and fracturing based on global positioning system data collected at Sheep Mountain anticline, Wyoming

Abstract: We investigate the curvature-fracture re lation ship at Sheep Mountain anticline, Wyoming, by coupling fracture mapping with structural mapping using high-precision global positioning system data. Carrier-phase post-processing techniques of spatial data collected across patches of bedding surfaces result in a high-resolution data set. Differential geometry tools form the basis for curvature analysis, allowing for a quantitative understanding of the shapes of these surfaces. Comparison of principal curvature ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Furthermore, there is a clear relationship between fracture permeability and curvature [69], and fracture porosity has been related to the product of bed thickness and curvature. Other studies have shown that zones of high fracture density coincide with areas of elevated curvature [70]- [73], a notion that is supported by the results of numerical modeling [74]- [80].…”
Section: Fracture Characterizationsupporting
confidence: 66%
“…Furthermore, there is a clear relationship between fracture permeability and curvature [69], and fracture porosity has been related to the product of bed thickness and curvature. Other studies have shown that zones of high fracture density coincide with areas of elevated curvature [70]- [73], a notion that is supported by the results of numerical modeling [74]- [80].…”
Section: Fracture Characterizationsupporting
confidence: 66%
“…The geomorphological study of deformed structures shows that the areas with highest fracture and faults densities broadly match those with highest absolute values of Gaussian curvature (Nelson, 2001). Recent studies (Allwardt et al, 2007) also confirm the correlation between high curvature values and fracture set orientations by coupling fracture mapping (GPS) with structural mapping.…”
Section: Curvature Analysismentioning
confidence: 74%
“…Most of set II veins are into this group, suggesting that this set was a poorly efficient conduit. Some veins from each set fall into these two fluid behaviors, suggesting that some early formed fractures were reopened and were hydraulically conductive at different times during fold growth, implying that in response to strata bending, some set I fractures were reopened [ Fiore Allwardt et al , 2007], while some set II veins were either reopened or newly formed during strata curvature [ Bergbauer and Pollard , 2004]. Further evidence for chemical solution of some set II veins comes from our observations of multiple generations of filling and dissolution (Figure 3c).…”
Section: Discussionmentioning
confidence: 99%
“…In this contribution, a study of the oxygen, carbon and strontium isotope composition of calcite veins and their host sedimentary rocks enables us to constrain the paleohydrological system evolution of the Sheep Mountain Anticline (SMA), a Laramide, basement‐cored anticline in Wyoming, United States (Figure 1a) [ Hennier , 1984; Forster et al , 1996; Stanton and Erslev , 2004; Stone , 2004; Erslev , 2005]. Even if the geometry of the underlying thrust is still debated [ Hennier and Spang , 1983; Forster et al , 1996, Stanton and Erslev , 2004; Stone , 2004, Fiore Allwardt et al , 2007, Amrouch et al , 2010a], the structure and timing of the fracture network in this fold is well constrained [ Harris et al , 1960; Johnson et al , 1965; Bellahsen et al , 2006a, 2006b; Amrouch et al , 2010a; Savage et al , 2010], and allows us to accurately place our geochemical study into a reliable spatiotemporal context related to the evolution of the fold. Our primary goal is to constrain the paleofluid system at the fold scale, and to relate the evolution of this system to the evolution of the fold.…”
Section: Introductionmentioning
confidence: 99%